Analisis Kerjasama Internasional dalam Membangun IKN: Bentuk, Fokus dan Kepentingan - Setiawan, Asep; Usni, Usni; Surwandono, Surwandono; Mediana, Dina; Syakban, Mansyur (Global Political Studies Journal, 2024)
This study analyses international cooperation, both bilateral and multilateral, in the establishment of Indonesia's new capital, Ibu Kota Nusantara (IKN). The study utilizes the theoretical frameworks of international collaboration and national interest to examine the dynamics that underpin these partnerships. A qualitative research methodology was employed, using data obtained from literature reviews and interviews. The results indicate three key insights. Initially, worldwide collaboration in the IKN project constitutes a commitment combining governmental bodies, the corporate sector, and global institutions. These interactions can be classified into form of bilateral and multilateral kinds of collaboration. Secondly, Indonesia's collaboration with partners from Asia and Europe focus two major areas: infrastructural development and ecologically sustainable practices. Asian nations have a robust interest in infrastructure projects, whilst European partners emphasize environmentally sustainable initiatives in the development of the new capital. Third, notwithstanding their participation in IKN, the economic and political objectives of Indonesia's partners from both Asia and Europe seem to transcend the initiative. Their main interest is to improve political and economic relations with Indonesia, frequently emphasizing investments in sectors like mining and infrastructure beyond the Kalimantan region. This study enhances the academic discourse regarding the patterns and modalities of international cooperation in Indonesia, providing insights into the strategic motivations of Indonesia's worldwide partners concerning the IKN project. Keywords — Bilateral, Cooperation, International, Multilateral, National interest, New capital city